Pengaruh Job Design dan Servant Leadership Terhadap Peningkatan Kinerja Karyawan KSPPS Bina Insan Mandiri Karanganyar - Amanda Gardiana Wibowo; Indra Hastuti; Khabib Alia Akhmad (CV. Muris Global Education, 2026)
This study aims to analyze the effect of job design and servant leadership on employee performance at KSPPS Bina Insan Mandiri Karanganyar. The background of this study is based on the importance of human resource management in Islamic cooperative organizations, where employee performance is a key factor in achieving organizational goals, particularly in member services and operational sustainability. This research employs a quantitative approach using data collected through a Likert-scale questionnaire distributed to 54 employees using a saturated sampling technique. Data analysis was conducted using validity and reliability tests, classical assumption tests, multiple linear regression, and hypothesis testing with SPSS. The results show that job design has a positive and significant effect on employee performance (t-value = 2.504; sig. 0.016), and servant leadership also has a positive and significant effect on employee performance (t-value = 5.768; sig. 0.000). Simultaneously, job design and servant leadership have a significant effect on employee performance (F-value = 22.546; sig. 0.000), with an Adjusted R Square value of 0.448, indicating that 44.8% of the variation in employee performance is explained by these two variables. In conclusion, better implementation of job design and servant leadership leads to improved employee performance at KSPPS Bina Insan Mandiri Karanganyar, making both factors important in organizational human resource management.